Cervicofacial actinomycosis with chronic parotid sialadenitis-mimicking malignant neoplasm of parotid gland: a rare case - Gaikwad, M. D.; Zainab, Bibi; Choudhary, Amir (International Journal of Research in Medical Sciences, 2024)
Cervicofacial actinomycosis is an uncommon disease caused by Actinomycosis israelii. Chronic ‘sialadenitis’ of parotid gland is an insidious inflammatory disorder and may form a fibrous mass. We report a case of 55 years old female presenting with mass in right parotid region-on imaging-malignant neoplasm of parotid gland. But on histopathology-actinomycosis and chronic parotid sialadenitis.